The Characteristics of Adjective Usage in the Language of Advertisements - Kamandulytė-Merfeldienė, Laura; Nenartavičiūtė, Skaistė (Respectus Philologicus, 2015)
The objectives of the study were to identify the semantic groups of the adjectives incorporated into the advertisements and to discuss the relationship between the adjective usage and manipulation strategy of the advertisements. A total number of 400 advertisements (totally 853 adjectives) have been taken from the newspapers Kauno diena, 15 min, Vakaro žinios and magazines Žmonės, Psichologija tau, Panelė, Cosmopolitan, Autocar, and Keturi ratai. The analysis revealed that most often the adjectives in the advertisements have the meanings of value, quality, and physical property. The general conclusion of this study is that advertisements in magazines are conveying information about gender differences through their language. The advertisers’ objective is to cater to women and men’s separate interests and their desires. The language used in male advertisements with fewer modifiers seems to be tougher and more straightforward, while the language in female magazines is more colourful. The adjectives used in male advertisements are precise and concrete; whereas, for female viewers – hyperbolised. They usually emphasize emotions, feelings, and femininity. The analysis of adjectives in the advertisements has shown that advertising does not only form stereotypes and images, but as well reflect peculiarities of contemporary world, consumer behaviour, and their specific features.